Ethnography at work - Moeran, Brian, 1944- (Berg, 2006)
Follows the experiences of the author as a participant observer in the running of a Japanese advertising agency. This book reveals the behind-the-scenes planning, discussion, negotiations and strategies needed to ensure that the agency's presentation to a potential client will be preferred over that of a rival firm.